834. Clinical Outcomes with Carbapenem-Resistant Pseudomonas aeruginosa that Retain Susceptibility to Traditional Antipseudomonal β-lactams: Atlanta, 2016-2018. (31st December 2020) - Howard-Anderson, Jessica; Bower, Chris W; Smith, Gillian; Satola, Sarah W; Jacob, Jesse T
Abstract: Background: Carbapenem-resistant Pseudomonas aeruginosa (CRPA) often results from multiple mechanisms, creating unique phenotypic patterns of resistance including retaining susceptibility to traditional antipseudomonal β-lactams: cefepime (FEP), ceftazidime (CAZ) and piperacillin-tazobactam (TZP). Outcomes of patients with CRPA susceptible to FEP, CAZ and TZP are unclear. Methods: The Georgia Emerging Infections Programed performs active, population-based surveillance for CRPA (minimum inhibitory concentration [MIC] ≥ 8 µg/mL for doripenem, imipenem or meropenem) isolated from sterile sites, urine, lower respiratory tracts and wounds in metropolitan Atlanta. We created a retrospective cohort of adults without cystic fibrosis with their first episode of CRPA while hospitalized or hospitalized within 1 week, from 8/2016 – 7/2018. We compared patients with CRPA that remained susceptible to FEP, CAZ and TZP ("susceptible CRPA") to those that were not ("resistant CRPA") including multivariable logistic regression for 30-day mortality. Results: Among 643 patients, 638 had susceptibility results available for FEP, CAZ or TZP. 60% were male, median age was 65 years, and median Charlson comorbidity index was 2 (Table 1). Most (66%) resided in a hospital or long-term care facility 4 days prior to culture. The most common source was urine (38%). Non-susceptibility to multiple antibiotic classes was common: 523 (81%) for 3 classes and 214 (33%) for 5 classes (Table 2). 220 (34%) patients had susceptible CRPA and compared to patients with resistant CRPA, were more likely to have lived in a private residence, have a community-associated infection, and less likely to be in the ICU previously (Table 1). Patients with susceptible CRPA had a similar crude 30-day mortality (16% vs 12%, p = 0.15) to those with resistant CRPA, but in a multivariable analysis had an increased 30-day mortality (OR 1.9; 95% CI 1.1–3.2). Table 1 (Part 1/2): Characteristics and outcomes of hospitalized patients with carbapenem-resistant Pseudomonas aeruginosa (CRPA) in metropolitan Atlanta, stratified by antipseudomonal β-lactam susceptibility Table 1 (Part 2/2): Characteristics and outcomes of hospitalized patients with carbapenem-resistant Pseudomonas aeruginosa (CRPA) in metropolitan Atlanta, stratified by antipseudomonal β-lactam susceptibility Table 2: Antibacterial susceptibility results for hospitalized patients with carbapenem-resistant Pseudomonas aeruginosa in metropolitan Atlanta Conclusion: Over 1/3 of hospitalized patients with CRPA retained susceptibility to other antipseudomonal β-lactams, but had an increased mortality compared to CRPA resistant to other β-lactams. Further research into mechanisms of resistance or antibiotics received might help explain this unexpected finding. Disclosures: Jessica Howard-Anderson, MD, Antibacterial Resistance Leadership Group (ARLG ) (Other Financial or Material Support, The ARLG fellowship provides salary support for ID fellowship and mentored research training)